Issues of Administrative Processing of Road Offences Detected by Weigh-in-Motion High-Speed Automatic System and Suggestions to Rationalising of this Administration - Bulíček, Josef; Kleprlík, Jaroslav; Světlá, Klára (Kaunas University of Technology, 2022)
The paper is focused on administrative processing of road offences detected by the weigh-in-motion high-speed automatic (HS-WIM) system. The aim of the paper is to suggest steps rationalizing technological process of this administration. The software tool of Microsoft Project is applied in the methodological point of view. The suggestions have been evaluated by using of data from the municipal authority of Říčany u Prahy as the locality with heavy traffic in Prague agglomeration. Time of administration of an offence is possible to be reduced by about 30% by applying of these suggestions. This is possible to be applied for rationalization of work at authorities responsible for road offences.
Otázky administrativního zpracování dopravních přestupků zjištěných automatickým systémem vysokorychlostního vážení a návrhy na racionalizaci této administrace
Keywords: detection of offences; high-speed weigh-in-motion; road offences; technological process of administrative processing of road offences; zjišťování přestupků; vysokorychlostní vážení; dopravní přestupky; technologický proces administrativního zpracování přestupku